Pengaruh Dana Alokasi Umum (DAU) terhadap Pertumbuhan Ekonomi di Kota Lhokseumawe - Maulena Maulena; Kheriah, Kheriah; Edi Abral (CV. Kalimasada Group, 2023)
This study aims to analyze the impact of General Allocation Funds (DAU) on economic growth, measured by the Gross Regional Domestic Product (PDRB) in Lhokseumawe City. The method used is simple linear regression, with DAU as the independent variable and PDRB as the dependent variable. The analysis reveals a positive and significant effect between DAU and PDRB, with a p-value of 0.004. These findings provide important insights for fiscal policy and regional financial management, indicating that an increase in DAU contributes to an increase in PDRB. The implication of these results is that effective fund allocation can support regional economic growth through investment in various development sectors.